Prevalence of Trematode Metacercariae in Cyprinoid Fish from Mae Lao District in Chiang Rai Province - สุนทราวิฑูร พิสิษฐ์; เจียมกิจวัฒนา เก่ง; ราชกิจ งามนิตย์ (KKU Science Journal, 2014)
A study of prevalence rate of trematode metacercariae was determined in cyprinoid fish collected from local markets, Mae Lao District, Chiang Rai Province from January to April 2013. A total of 267 freshwater fish of 7 species were examined by dissection and compression techniques. The overall prevalence rate of metacercariae in cyprinoid fish was 71.2% (190/267), predominantly in Mystacoleucus marginatus (100%), Henicorhynchus siamensis (84.8%), Labiobarbus siamensis (77.4%), Barbonymus gonionotus (62.8%), Barbonymus schwanenfeldii (48.3%), Osteochilus vittatus (26.7%) and Thynnichthys thynnoides (0.0%), respectively. Haplorchis taichui metacercariae was found in the highest number followed by Haplorchoides spp. and unidentified species of metacercariae, respectively. The highest intensity of Haplorchis taichui metacercariae infection in Henicorhynchus siamensis was 28.9. These results indicate that eating raw freshwater fish represents a high risk for acquiring fishborne zoonotic trematode infection in Chiang Rai Province.